Accountability of State Financial Management (Study at the Faculty of Social Sciences and Law, Universitas Negeri Manado) - Wowor, Wissje J. D.; Sendouw, Recky H. E.; Kantohe, Meidy (Technium Social Sciences Journal, 2023)
The aim to be achieved in this research is to find out, analyze, and describe the Financial Management Accountability of Public Service Agencies (BLU) at the Faculty of Social Sciences and Law (FISH) Universitas Negeri Manado (Unima). The research method uses a qualitative descriptive approach. Informants were determined using purposive sampling. Data were analyzed descriptively and qualitatively. Data collection techniques use observation, interviews, and documentation. The data analysis techniques that will be used in this research consist of data reduction, data presentation, and drawing conclusions. The results of the research show that the process of preparing planning documents up to Budget Planning looks good, but in the future, the coordination of the preparation of activities between Departments, study programs, Faculties, and Universities, can still be improved. Meanwhile, in budget implementation, efforts are still needed to reduce or simultaneously eliminate obstacles in the submission of Accountability Letters (SPJ) from departments and study programs, so that they do not hinder the implementation of other activities due to negligence in SPJ matters. In Budget Accountability, the role of Faculty leaders is still needed in monitoring the preparation of activity reports and the placement of human resources who have competence in preparing reports. This needs attention because negligence in financial management accountability has legal consequences.